THE COMMUNICATION MEDIA OF DALIHAN NA TOLU IN THE MARRIAGE TRADITION OF MANDAILING ETHNIC IN MANDAILING NATAL REGENCY - Rahmi Wahyuni (Program Pascasarjana UIN Sumatera Utara, 2021)
This study aims to discover the communication media Dalihan Na Tolu in the marriage tradition of Mandailing Ethnic in Mandailing Natal regency. This study applied descriptive qualitative. The direct observation in the field was employed to obtain the data by doing a sequence of stages namely observing and watching the marriage tradition procession from the beginning until the end, in-depth interview to some traditional figures and documentation related to the research. The result of the study demonstrates two media are used in the communication media Dalihan Na Tolu in the marriage tradition of Mandailing Natal ethnic, they are traditional media and modern media. The traditional media consists of sirih (betel), salipi, gondang tunggu-tunggu, ogung, and pangupa. Moreover, the modern media consists of wedding invitation card, flower board, telephone, smartphone, social media and radio.